Titanic at 100 [videorecording (DVD)] : mystery solved - Bacon, Tony; DeNooyer, Rushmore (History ; Distributor] New Video, 2012)
A fascinating feature-length documentary, 'Titanic at 100' will take viewers on a journey to the bottom of the North Atlantic where they will investigate the remains of the most famous ship in history. Produced in conjunction with the Woods Hole Oceanographic Institute and RMS Titanic, Inc., this special provides the most authoritative look at the shipwreck, and is timed to the 100th anniversary of the sinking.